Understanding schizophrenia : a practical guide for patients, families, and health care professionals - Reddy, Ravinder; Keshavan, Matcheri S., 1953- (Santa Barbara, California : Praeger, an imprint of ABC-CLIO, LLC, 2015)
This concise and up-to-date guide to schizophrenia focuses on dealing with many aspects of the illness--complying with treatment, managing crises, being a caregiver, communicating with the care team, and coping skills. It also provides practical approaches to common issues such financial support, housing, employment, interacting with the legal system, stress management, socialization, and negative emotions.--From publisher description.
Facing schizophrenia : quick primer -- Core clinical features of schizophrenia -- What is not schizophrenia? -- Who gets schizophrenia? -- How is schizophrenia diagnosed? -- What is the course and prognosis of schizophrenia? -- Medical treatment of schizophrenia -- Common medication side effects -- Psychological and rehabilitative treatments -- Treatment nonadherence -- Achieving maximal recovery -- Life with schizophrenia -- Assembling your care team -- A manual for caregivers -- Common problems in facing schizophrenia -- Managing crises -- Biological foundations of schizophrenia -- What does the future hold? -- Appendix A: Commonly used antipsychotics for schizophrenia -- Appendix B: Very brief history of schizophrenia -- Appendix C: Recommended resources -- Appendix D: Forms and lists.
Includes bibliographical references and index.
Keywords: Schizophrenia -- Popular works; Consumer education